Ethnolinguistics of Madurese Language Preservation through Oral Literature in Lok-Olok Art - fauziah, Arinal Haq (Journal of Language, Literature and Teaching, 2024)
In facing the challenges of globalisation and modernisation, the preservation of local language and culture, especially the Madurese language, is becoming increasingly important. This research focuses on the oral literature tradition of Lok-Olok as an effort to maintain and preserve the Madurese language. Lok-Olok is a poem or verse spoken in the Karapan Sapi performance. The art of Lok-Olok not only reflects the beauty of language, but also conveys the cultural values and identity of Madurese society. This research uses a qualitative approach with ethnomethodology method to understand the role and meaning of Lok-Olok in the context of language preservation. Through interviews with tokang lok-olok and observation, this research explores how oral literature becomes a reinforcement and preservation of the Madurese language. The results show that the involvement of the younger generation in Lok-Olok is very important to foster a love for Madurese language and culture. By understanding and preserving Lok-Olok, it is hoped that the Madurese language can survive and remain relevant in the modern era. This research provides insight into the importance of preserving oral literature as part of efforts to maintain the sustainability of the Madurese language.